2017
DOI: 10.1002/anie.201709285
|View full text |Cite
|
Sign up to set email alerts
|

Access to α‐Amino Acid Esters through Palladium‐Catalyzed Oxidative Amination of Vinyl Ethers with Hydrogen Peroxide as the Oxidant and Oxygen Source

Abstract: A novel and convenient palladium catalytic system for the synthesis of α-amino acid esters from simple starting materials is reported. Hydrogen peroxide not only acts as the green oxidant, but also as the oxygen source. This strategy for the conversion of amines and vinyl ethers into highly functionalized and structurally diverse α-amino acid esters is characterized by the simplicity of the experimental procedure, mild reaction conditions, high atom economy, scalability, and practicability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…Simultaneously, our research also extended to another green oxidant: H 2 O 2 . In 2017, we demonstrated a highly innovative and convenient palladium‐catalyzed oxidative amination of amines with vinyl esters, and plentiful functionalized α‐amino acid esters (Scheme ) . Notably, 18 O‐labeling experiments suggested that H 2 O 2 acted as a green oxidant and oxygen source (Scheme ).…”
Section: H2o2 or Tbhp As The Oxidantmentioning
confidence: 99%
See 4 more Smart Citations
“…Simultaneously, our research also extended to another green oxidant: H 2 O 2 . In 2017, we demonstrated a highly innovative and convenient palladium‐catalyzed oxidative amination of amines with vinyl esters, and plentiful functionalized α‐amino acid esters (Scheme ) . Notably, 18 O‐labeling experiments suggested that H 2 O 2 acted as a green oxidant and oxygen source (Scheme ).…”
Section: H2o2 or Tbhp As The Oxidantmentioning
confidence: 99%
“… Proposed catalytic cycle for the palladium‐catalyzed oxidative amination of amines with vinyl esters …”
Section: H2o2 or Tbhp As The Oxidantmentioning
confidence: 99%
See 3 more Smart Citations